Picturesque of Literature and Literature of Fine Arts in Works of Twice Exceptional Expressionists - Varetska, Sofiya (Pitannâ lìteraturoznavstva, 2020)
The article considers a problem of the arts interaction, which is a characteristic feature of German expressionism. It analyzes works of gifted expressionists, which are fulfilling themselves not only as writers, but as painters too and vice versa. All attention is paid to such figures of expressionism as Oscar Kokoschka, Franz Kafka, Alfred Kubin. The article argues that the power of talent of such artists is so great that self-realization in one of the arts is not enough for them, and therefore they actively use the opportunity to reveal the facets of their giftedness not only verbally, but also visually, alternately changing brushes to pen. Such a synthesis is quite productive because these works are enriched by narrative thematic motifs, genre varieties, a figurative vision of reality, compositional figures of the material organization, etc. It is proved that the expressionists did not follow the modernist concept “Art for the sake of art”, yet for them a human is with his fears, complexes and visions in the center. Thus, the main aim of an artist is using various artistic means to show a sacred inner world where in contrast to the real philistine life a spiritual unity and harmony do exist. In a combination of text, drawing or music, or, like Kokoschka’s light and paint, expressionists try to convey through multimedia the sensual and sacred that arises for them as the purpose of existence.